Factors affecting empathy among indian dentists - Soni Rajput; Manjunath P Puranik; Namita Shanbhag; Amit Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: Empathy is one of the major essential elements in patient and dentist relationship. Interpersonal Reactivity Index (IRI) has been used extensively to measure empathy among medical and other health professions. However, its validity in dental profession remains to be explored. Aims: To examine the psychometric properties of IRI and also to assess the factors influencing the dental students' empathy. Setting and Design: A cross-sectional questionnaire study was carried out among 100 dental interns and postgraduates using IRI. Materials and Methods: Patients were selected randomly from six dental colleges in Bangalore. Internal consistency of items was evaluated by Cronbach's alpha and construct validity was assessed by confirmatory factor analysis with an orthogonal varimax rotation of factors. Statistical Analysis Used: The data were evaluated using SPSS 22. Descriptive and inferential statistics were performed with significance set at 5%. Results: Internal consistency of IRI (Cronbach's alpha: perspective taking = 0.76, fantasy = 0.80, empathic concern = 0.72, and personal distress = 0.79) was good. A four-factor solution emerged, accounting for 52% of total variance. The mean age of the participants was 24.25 ± 1.95 years. The mean for empathic concern domain was highest (20.75 ± 1.64). Gender, career choice, academic performance, and work satisfaction were associated with increased empathy scores, whereas depression and stress were associated with decreased empathy scores (P < 0.05). Conclusion: This study confirms the construct validity and reliability of the IRI for assessing empathy in dental students. Empathy scores among students varied depending on professional/personal factors.